Long-term Outcomes of Patients With Human Herpesvirus 6 Encephalitis. (5th June 2019) - Fida, Madiha; Hamdi, Ahmed M; Bryson, Alexandra; Razonable, Raymund R; Abu Saleh, Omar
Abstract: Human herpesviruses 6 (HHV-6) A and B cause encephalitis in patients with hematologic malignancies, especially those undergoing allogeneic hematopoietic stem cell transplantation. In this cohort of 10 patients, persistent neurologic deficits associated with moderate to severe bilateral hippocampal atrophy were characteristic long-term findings, despite prolonged antiviral treatment.